Подъемно-транспортные машины: [учеб. для машиностроит. техникумов] / Александров М. П. - Александров Михаил Павлович (Машиностроение, 1984)
Экземпляры: КХ (20051223) / Инвентарный номер: 841872 / Сис.шифр: 621.87 / Авт.знак: А 46 / ГРНТИ: 55 / ББК: 3